Report on Southern Regional Research-Extension-Linkage Committee’s (RELC’s) Planning Sessions, Ghana - Anku, Prospera; Addo, Bridgette Ofosua; Dalaa, Mustapha Alasan; Obeng, Faustina; Kyere, Reginald (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The regional Research-Extension-Linkage Committees (RELCSp) lanning sessions are platforms where various stakeholders in agriculture sector assemble to deliberate on constraints that facing Ghana’s agricultural system. It also assesses the performance of the year’s agricultural activities under the RELCs within the regions. The Directorate of Agricultural Extension Services (DAES) in collaboration with the Council for Scientific and Industrial Research (CSIR) with support from the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA coordinated the organization of the Regional RELC Planning Sessions for five regions namely Ashanti, Bono, Western, Central and Greater Accra). As part of the operationalisation of the Ghana National Framework for climate services, AICCRA Ghana cluster and USAID PolicyLINK feed the future Projects organised these planning sessions in ten (10) regions to help mainstream Climate Information Services in National Agriculture extension system. This report is thus focused on five (5) out of the ten (10) regions AICCRA directly supported. This partnership also saw the onboarding of Climate Information Service providers from the public and private sectors to the platform. Representatives from Directorate of Agric Extension Services of MoFA , Ghana Meteorological Agency (GMet), the Council for Scientific and Industrial Research (CSIR) , and AICCRA participated and technically backstopped in the regional RELC planning sessions . Other stakeholders included farmers, input suppliers, departmental heads from state and non-state actors in agriculture sector.